2013
DOI: 10.1179/2045772312y.0000000023
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte colony-stimulating factor reduced neuropathic pain associated with thoracic compression myelopathy: Report of two cases

Abstract: Context: A clinical trial was conducted to evaluate the safety and efficacy of neuroprotective therapy using granulocyte colony-stimulating factor (G-CSF) for patients with worsening symptoms of compression myelopathy. During this trial, we found that neuropathic pain associated with thoracic myelopathy was dramatically reduced after G-CSF administration in two cases. Findings: A 32-year-old man with compression of the spinal cord at levels T7-T10 complained of spastic gait associated with spontaneous severe p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…Therefore, the effect of CeONPs, on the neural markers ERK1/2 and Tau could possibly be explained by its ROS scavenging properties. The expression of GCSF, which inhibits neuropathic pain [44][45][46], was higher in the treatment group compared to the SCI group, but this increase was not statistically signi cant in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…Therefore, the effect of CeONPs, on the neural markers ERK1/2 and Tau could possibly be explained by its ROS scavenging properties. The expression of GCSF, which inhibits neuropathic pain [44][45][46], was higher in the treatment group compared to the SCI group, but this increase was not statistically signi cant in our study.…”
Section: Discussioncontrasting
confidence: 78%
“…In more recent human clinical trials, several studies have used G-CSF as a treatment for neuromuscular disease with promising results for muscle-related functional outcomes. Specifically, Sakuma et al [ 81 ] and Yamazaki et al [ 82 ] demonstrated improved neurological function after treatment with 10 μ g/kg G-CSF in subjects with thoracic myelopathy. This is in line with this group's previous work [ 83 , 84 ] where improvements in motor function following spinal cord injuries in rodents were observed.…”
Section: The Role Of G-csf In Skeletal Musclementioning
confidence: 99%
“…Our previous animal studies and several similar studies have shown that granulocyte colony stimulating factor (GCSF) treatment can attenuate neuropathic pain in rats that undergo chronic constriction injury (CCI) and spinal cord injury [1][2][3][4]. Human clinical trials have also demonstrated the analgesic effects of GCSF in patients with compressive myelopathy [5,6]. In our recent studies, an early GCSF treatment was shown to recruit opioid-containing polymorphonuclear granulocytes (PMNs) to the injury site from 12 to 48 h after nerve injury, upregulate mu opioid receptor (MOR) expression on the injured nerve on days 1-3 after nerve injury, suppress proinflammatory cytokines (IL-6 and TNF-α) in the dorsal root ganglia (DRGs) on days 2-6 after nerve injury, downregulate phosphorylated p38 on day 3 after nerve injury and activated microglia on days 3-6 after nerve injury in the spinal dorsal horn, decrease IL-6 (pro-inflammatory cytokine) but increased IL-4 (anti-inflammatory cytokine) levels from days 1 to 7 in the spinal dorsal horn (SDH) after nerve injury and thus attenuate neuropathic pain development in CCI rats [1,2] (Figure 1).…”
Section: Introductionmentioning
confidence: 96%